Role of mechanical strain and estrogen in modulating osteogenic differentiation of mesenchymal stem cells (MSCs) from normal and ovariectomized rats - Li, L.; Yao, X. L.; He, X. L.; Liu, X. J.; Wu, W. C.; Kuang, W.; Tang, M. (Cellular and Molecular Biology, 2013)
Bone’s adaptability to loading depends upon the process of bone remodeling. This adaptive mechanism is restricted in postmenopausal osteoporosis. Differentiation of mesenchymal stem cells (MSCs) is crucial to bone remodeling and regeneration. It is well accepted that mechanical loading influences the fate of MSC differentiation. The aim of this study was to explore the possible restricted mechanism in osteoporotic condition, through investigating response of MSCs from both sham-operated and ovariectomized rats. MSCs were exposed to estrogen and mechanical strain (2%, 1Hz, 6h/day) for 3 days. Osteogenic differentiation and Î²-catenin protein in MSCs were examined. Exposure to estrogen and mechanical strain alone enhanced expression of Runx2 (CbfÎ±1), type I collagen (ColI) and activated Î²-catenin protein in MSCs from both sham-operated and OVX rats. MSCs from both sham-operated and OVX rats stimulated with both mechanical strain and estrogen had higher expression of osteogenic genes and activated Î²-catenin protein than these cells exposed to estrogen and mechanical strain alone. Osteoporotic MSCs had lower expression of osteogenic genes and protein in the absence and presence of stimulation than did MSCs from sham-operated rats. Cumulatively, our results indicate that mechanical strain and estrogen in vitro enhance osteogenic potential and activation of Î²-catenin in MSCs from both sham-operated and OVX rats. Estrogen augments strain-induced osteogenic potential and activity of Î²-catenin in MSCs.